Novel Synergistic Approach for Bioactive Macromolecules: Evaluating the Efficacy of Goat Placenta Extract in PEGylated Liposomes and Microspicules for Chemotherapy-Induced Hair Loss - Phitjira Sanguanboonyaphong; Phaijit Sritananuwat; Sureewan Duangjit; Anyamanee Lapmag; Watcharin Pumchan; Tanasait Ngawhirunpat; Praneet Opanasopit; Worranan Rangsimawong (MDPI AG, 2024)
Chemotherapy-induced hair loss is a distressing side effect of cancer treatment, and medical interventions are often needed to address this problem. The objectives of this study were to evaluate the bioactivity of goat placenta (GP) extract on both normal and chemotherapy-induced hair cells and to develop PEGylated liposomes (PL) and microspicule (MS) formulations for promoting hair growth in patients with chemotherapy-induced hair loss. The bioactivities of GP extract on human follicle dermal papilla (HFDP) cells and cells damaged by chemotherapy were assessed. GP extract was incorporated into PLs and MS gel (PL-MS) and then investigated in vitro skin permeation and in vivo studies on the scalps of patients with chemotherapy-induced hair loss. GP extract stimulated HFDP cell proliferation in both normal and cisplatin-damaged cells. PL nanovesicles and MS gel worked synergistically to deliver macromolecular proteins into the skin and hair follicles. The application of GP extract-loaded PL-MS to the scalps of chemotherapy-treated patients for 12 weeks significantly enhanced the hair growth rate, without causing skin irritation. In conclusion, GP extract promoted the proliferation of hair cells damaged by chemotherapy, when this extract, combined with PL-MS, effectively delivered bioactive macromolecules across the skin and hair follicles, resulting in successful regrowth of hair post-chemotherapy.